ПИТАННЯ РОЗРОБЛЕННЯ МОДЕЛЕЙ СИСТЕМНОЇ АВТОМАТИКИ ДЛЯ ДОСЛІДЖЕННЯ АВАРІЙНИХ РЕЖИМІВ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМ - О.Ф. Буткевич; Т.М. Гурєєва; Н.Т. Юнєєва (Праці Інституту електродинаміки Національної академії наук України)
The peculiarities of the approach used to the development of digital models of system automation devices for power systems fault condition simulation are considered. Some issues related to the practical development of digital models of system automation devices of power systems are briefly outlined. The role of the graphical interface as a tool for pre-paring such models and manipulating them is shown. Using the examples of automatic frequency unloading and auto-matic elimination of asynchronous modes, the peculiarities of the functioning and setting up of the models are analyzed. The results of the use of the developed models during the Interconected power system (IPS) of Ukraine fault condition simulation are presented. The results of the use of the developed automatic elimination of asynchronous modes during the simulation of emergency modes of the IPS of Ukraine with the detection of the electrical center of oscillations on the 750 kV and 330 kV power transmission lines in the Western and South-Western power system are presented. To check the adequacy of the automatic frequency unloading models, the data obtained from the regional power systems of Ukraine were used, the simulated emergency disturbances led to a shortage of active generating power and a decrease in frequency, as a result of which the automatic frequency unloading devices were activated. Ref. 3, fig. 8.